Microwave-Assisted Synthesis of Bis(dihydropyrimidinone)benzenes - Mirza, Behrooz; Sargordan, Mohsen; Fazaeli, Reza (Asian Journal of Chemistry, 2011)
Bis(dihydropyrimidinonoe)benzenes were synthesized in good to high yields by a pseudo fourcomponent reaction of a dialdehyde such as terephthalic aldehyde or isophthalic aldehyde, (thio)urea and 1,3-dicarbonyl compounds using reusable nanosilica (average particle size ca. 50 nm, BET specific surface area (SSA) > 200 m2/g as catalyst), under microwave irradiation in solvent-free conditions. Inexpensive reusable catalyst, low energy consumption, high yields of the products and simple work-up are attractive features of this green protocol.